Literature, Book, Computer and Narration. Models and Shapes of Electronic Literature - Federico Meschini (JLIS.it, 2020)
This article reports on an analysis of the different forms and practices of electronic literature starting with the concept of the ebook as the zero degree of literary re-mediation. The next step is the use of a computational model (composed of data, processes, interactions, a user interface, and context) applied to a semiotic model of the book in which one goes from the physicality of the signs on the page to the abstract concept of the work so as to classify the various types of electronic literature from hypertextual works to digital poetry to twitterature to the automatic creation of texts and finally returns to the relationship with the printed book and the mutual influence between the various communicative genres. This study also contains an analysis of recent literary works such as S., theMystery.doc, and House of Leaves in which the limits of the typographic page are challenged and the linearity of the text is shattered. Thus it shows how digital textuality is reflected in aspects ranging from the book as an object to the form of the novel and how electronic literature is an integral part of the redefinition of cultural and communicative processes.